2014
DOI: 10.1002/ejhf.102
|View full text |Cite
|
Sign up to set email alerts
|

EAARN score, a predictive score for mortality in patients receiving cardiac resynchronization therapy based on pre‐implantation risk factors

Abstract: AimsThe beneficial effects of CRT in patients with advanced heart failure, wide QRS, and low LVEF have been clearly established. Nevertheless, mortality remains high in some patients. The aims of our study were to identify the predictors of mortality in patients treated with CRT and to design a risk score for mortality.Methods and resultsA cohort of 608 consecutive patients treated with CRT from 2000 to 2011 in our centre was prospectively analysed. Baseline clinical and echocardiography variables were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 29 publications
6
51
0
1
Order By: Relevance
“…Some studies [5] do not show differences in mortality in older and younger patients. Other works [6] show that a greater age is a risk factor for higher mortality, together with other data (New York Heart Association functional class IV, impaired renal function, atrial fibrillation, and left ventricular ejection fraction <22%). With this doubt, the implantation of these devices could be considered in patients with advanced functional stages and older age.…”
Section: Predictors Of Response To Cardiac Resynchronization Therapymentioning
confidence: 64%
“…Some studies [5] do not show differences in mortality in older and younger patients. Other works [6] show that a greater age is a risk factor for higher mortality, together with other data (New York Heart Association functional class IV, impaired renal function, atrial fibrillation, and left ventricular ejection fraction <22%). With this doubt, the implantation of these devices could be considered in patients with advanced functional stages and older age.…”
Section: Predictors Of Response To Cardiac Resynchronization Therapymentioning
confidence: 64%
“…Three other simple scores proved to readily predict survival after CRT. The EAARN score, a simple score based on LVEF, age, atrial fibrillation, renal dysfunction, and NYHA class IV had a significant add‐on predictive effect with regard to mortality, but has not been externally validated . The HF‐CRT score, which combined clinical and readily available biomarker data, stratified CRT patients for HF progression and death .…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper identified NYHA functional class IV, eGFR <60 ml/min/1.73m 2 , age ≥70 years, atrial fibrillation and ejection fraction <22% to be associated with mortality over a mean follow-up of 36.2 ± 29.2 months (8). Another study looking at predictors of long-term mortality in CRT found larger left ventricular end-systolic volume, less distance covered in the 6 min walking test, poor renal function, more severe heart failure, male gender, and presence of atrial fibrillation, no posterolateral left ventricular (LV) lead, and no LV dyssynchrony to be associated with poor prognosis after CRT (9).…”
Section: Discussionmentioning
confidence: 99%
“…These prior risk modeling studies have been limited by highly selected patient groups and the absence of serum biomarkers now known to play an integral role in HF progression (8,9). We sought to identify predictors of mortality and early need for advanced circulatory support interventions among the cohort of primary prevention CRT-defibrillator (CRT-D) recipients in the Prospective Observational Study of Implantable Cardioverter-Defibrillators (PROSE-ICD).…”
Section: Introductionmentioning
confidence: 99%